Direct Medical Cost Analysis Among Coronary Heart Disease and Heart Failure Outpatients at One Hospital - Nunik Dewi Kumalasari; Abdul Rahem; Bobby Presley; Eko Setiawan (Faculty of Pharmacy, Universitas Gadjah Mada)
Long-term treatment of cardiovascular disease may give impact in a high burden of medical cost for the patient. A concern arises whether the health budget allocation prepared by the Indonesian Government through